Endogenous Sox8 is a critical factor for timely remyelination and oligodendroglial cell repletion in the cuprizone model - Freudenstein, David; Lippert, Magdalena; Popp, Janina Sophie; Aprato, Jessica; Wegner, Michael; Sock, Elisabeth; Haase, Stefanie; Linker, Ralf A.; González Alvarado, María Nazareth (Scientific Reports, 2023)
Genome-wide association studies identified a single nucleotide polymorphism (SNP) downstream of the transcription factor Sox8, associated with an increased risk of multiple sclerosis (MS). Sox8 is known to influence oligodendrocyte terminal differentiation and is involved in myelin maintenance by mature oligodendrocytes. The possible link of a Sox8 related SNP and MS risk, along with the role of Sox8 in oligodendrocyte physiology prompted us to investigate its relevance during de- and remyelination using the cuprizone model. Sox8−/− mice and wildtype littermates received a cuprizone diet for 5 weeks (wk). Sox8−/− mice showed reduced motor performance and weight compared to wildtype controls. Brains were histologically analysed at the maximum of demyelination (wk 5) and on two time points during remyelination (wk 5.5 and wk 6) for oligodendroglial, astroglial, microglial and myelin markers. We identified reduced proliferation of oligodendrocyte precursor cells at wk 5 as well as reduced numbers of mature oligodendrocytes in Sox8−/− mice at wk 6. Moreover, analysis of myelin markers revealed a delay in remyelination in the Sox8−/− group, demonstrating the potential importance of Sox8 in remyelination processes. Our findings present, for the first time, compelling evidence of a significant role of Sox8 in the context of a disease model.
CRIS-Team Scopus Importer:2023-12-22

Myrf as a molecular switch for target gene selection of Sox10 during oligodendroglial development - Aprato, Jessica; Küspert, Melanie; Weider, Matthias; Fröb, Franziska; Wegner, Michael (GLIA, 2019)
CRIS-Team WoS Importer:2020-01-10

Myrf guides target gene selection of transcription factor Sox10 during oligodendroglial development - Aprato, Jessica; Sock, Elisabeth; Weider, Matthias; Elsesser, Olga; Fröb, Franziska; Wegner, Michael (Nucleic Acids Research, 2020)
Oligodendrocytes generate myelin in the vertebrate central nervous system and thus ensure rapid propagation of neuronal activity. Their development is controlled by a network of transcription factors that function as determinants of cell identity or as temporally restricted stage-specific regulators. The continuously expressed Sox10 and Myrf, a factor induced during late development, are particularly important for terminal differentiation. How these factors function together mechanistically and influence each other, is not well understood. Here we show that Myrf not only cooperates with Sox10 during the induction of genes required for differentiation and myelin formation. Myrf also inhibits the activity of Sox10 on genes that are essential during earlier phases of oligodendroglial development. By characterization of the exact DNA-binding requirements of Myrf, we furthermore show that cooperative activation is a consequence of joint binding of Sox10 and Myrf to the same regulatory regions. In contrast, inhibition of Sox10-dependent gene activation occurs on genes that lack Myrf binding sites and likely involves physical interaction between Myrf and Sox10 followed by sequestration. These two opposite activities allow Myrf to redirect Sox10 from genes that it activates in oligodendrocyte precursor cells to genes that need to be induced during terminal differentiation.
CRIS-Team WoS Importer:2020-03-10

Sox8: a multifaceted transcription factor in development and disease - González Alvarado, Marıá Nazareth; Aprato, Jessica (Biology Open, 2025)
Sox8 is a transcription factor that belongs to the Sox family of high-mobility-group domain containing proteins and is closely related to Sox9 and Sox10. During prenatal development, Sox8 is expressed in several ectoderm-, endoderm- and mesoderm-derived tissues and has been implicated in processes of organogenesis and differentiation. Sox8 expression is found in several important cells such as Sertoli cells in the male gonad, glial cells, satellite cells, and chondrocytes. However, Sox8 is not essential for the proper development of any of the involved systems, as it functions redundantly with Sox9 or Sox10 and no major developmental disturbances have been noticed in its absence. Despite its perceived limited importance as a developmental regulator, Sox8 exhibits a more significant role in late development and adult tissues. Several studies highlight the importance of Sox8 for the homeostasis of adipose tissue, Sertoli cells and the blood-testis-barrier functioning, and the maintenance of myelin in the central nervous system. Emerging evidence points to SOX8 as a promising candidate for a disease-causing gene in humans and suggests that changes in SOX8 function or expression could contribute to pathological states. For instance, genetic variants of SOX8 have been linked to multiple sclerosis and familial essential tremor, while SOX8 alterations have been related to poor cancer prognosis and infertility. This Review provides an overview of Sox8’s versatile role in development and adult tissues as well as its lesser-known contributions to various diseases, and its potential as a therapeutic target.
CRIS-Team Scopus Importer:2025-04-01
Keywords: Development; Disease; Nervous system; Sex determination; Sox8; Transcription factor